Exploring the Social Impact of the Short-Stay Market (SSM) in Regional Areas: An Empirical Study - Ndaguba, Emeka; Brown, Kerry; Marinova, Dora; Jogulu, Uma (2023)
The discourse on microentrepreneurs and their involvement in the short stay market (SSM) was non-existent until 2008. While several concepts and constructs have been developed and empirically tested since 2009, many of them relate to economics, leaving the social, cultural, and environmental factors underdeveloped. Thus, this study aimed to fill the gap and identify and assess the social impact of the short-stay market (SSM) in a regional area. The study included 16 face-to-face interview sessions conducted with 18 participants, and the Leximancer software was employed to analyse the data. The study revealed that the social impact on SSM is not generic, rather pluralistic, multidimensional, and dynamic. The study also found that the limitation clause instituted by the council is a direct disconnect between the council and property owners/managers. Furthermore, despite ample opportunities provided by the short-stay market (SSM) in regional areas, encumbrances cannot be overlooked. Therefore, there is a need for a comprehensive approach to understand the social impact on policy frameworks in regional areas.